Overview: methods and applications for droplet compartmentalization of biology - Leamon, John H; Link, Darren R; Egholm, Michael; Rothberg, Jonathan M (Nature methods, 2006)
Three protocols in this issue highlight applications of emulsification procedures, which deliver high-throughput potential to the molecular biology laboratory, without the need for automation. These procedures have already generated interesting results and spurred the development of exciting new technologies, while requiring only readily available laboratory equipment.